RELATIONSHIP OF BASE COMPONENTS OF EXECUTIVE FUNCTIONS AND THE DEVELOPMENT OF READING UNDERSTANDING: A VIEW OF NEURO LEARNING - de Melo Zito, Vanessa (Revista Gênero e Interdisciplinaridade, 2022)
The theme of the present study is the integration between executive functions and comprehensive reading, considering the neuro-learning. Executive functions are a set of cognitive skills that enable the individual to plan, regulate, execute actions, thoughts and emotions at the expense of a goal. The comprehensive reading involves the recognition of a word and the extraction of its meaning, and for this it requires the identification of the letters, recognition of the word, access to the meaning, syntactic and semantic integration, numerous cognitive processes, among them, the integration of executive functions. Thus, the objective was to correlate the constructs of executive functions and reading comprehension, considering neuro-learning. For this purpose, a literature review was carried out, based on books of neuro-learning from the last 20 years, and articles from Scielo, Academic Google, Pubmed and Virtual Health Library databases, conducting a survey based on keywords, executive functions, reading and comprehensive reading from the last 10 years. Therefore, it was concluded that language skills, such as oral language, phonological awareness and word recognition are essential for reading and understanding, however other cognitive processes are also involved in this complex activity, in particular the executive functions, which proved to be fundamental for the reader to understand a text effectively.